Assistance in Establishing a Garbage Bank for Urban Communities Based on Community Assets, in Wonokusumo Kidul Surabaya - Wahanani Mawasti (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
This study aims to describe the stages of assisting the establishment of waste banks in urban areas. This is based on the existence of problems in urban areas, especially in the field of environment (settlements) and economy. The approach used in the implementation of mentoring is community asset-based community development. The role of the companion as a facilitator in the process of social change in the community. The results showed the success of community empowerment in urban areas by utilizing community assets. This success took the form of the establishment of the